2010
DOI: 10.1111/j.1399-0039.2009.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of DLA class II haplotypes in canine diabetes mellitus through single nucleotide polymorphism genotyping

Abstract: Strong linkage disequilibrium (LD) is a characteristic of the major histocompatibility complex (MHC) region, as well as the genome in general in dogs as a consequence of demographic changes with domestication. Disease association studies of MHC haplotypes may be affected by high LD and the resultant shared genetic backgrounds of haplotypes giving associations with linked but non-causative mutations, and also by convergent haplotypes, in which combinations of alleles have arisen independently. This study provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Since both linkage disequilibrium (LD) and allelic content vary for different HLA haplotypes (Horton et al, 2008), this may be true for the DLA. The exon 2 ‘alleles’ may represent different haplotypes that appear to be identical due to convergence (Seddon et al, 2010). When Seddon et al (2010) sampled SNPs from the MHC class II region to evaluate canine cases and controls for type I diabetes, it was concluded that the published class II association with type I diabetes (Kennedy et al, 2006a), could be outside the DRB1/DQA1/DQB1 exon 2 region or within a region larger than just exon 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since both linkage disequilibrium (LD) and allelic content vary for different HLA haplotypes (Horton et al, 2008), this may be true for the DLA. The exon 2 ‘alleles’ may represent different haplotypes that appear to be identical due to convergence (Seddon et al, 2010). When Seddon et al (2010) sampled SNPs from the MHC class II region to evaluate canine cases and controls for type I diabetes, it was concluded that the published class II association with type I diabetes (Kennedy et al, 2006a), could be outside the DRB1/DQA1/DQB1 exon 2 region or within a region larger than just exon 2.…”
Section: Discussionmentioning
confidence: 99%
“…The exon 2 ‘alleles’ may represent different haplotypes that appear to be identical due to convergence (Seddon et al, 2010). When Seddon et al (2010) sampled SNPs from the MHC class II region to evaluate canine cases and controls for type I diabetes, it was concluded that the published class II association with type I diabetes (Kennedy et al, 2006a), could be outside the DRB1/DQA1/DQB1 exon 2 region or within a region larger than just exon 2. It is also possible that associations are more complex than those involving a single haplotype (Seddon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In dogs, only one study has been conducted on the MHC class II promoters and their role in the regulation of the MHC class II genes (23). In canine diabetes mellitus, both protective and susceptibility MHC class II haplotypes have been found, suggesting a complex interaction between the MHC class II and canine diabetes mellitus (23). In this study, a variable site was identified within the promoter DQBp X1‐box, where protective alleles in diabetic dogs, but not in other dogs, had an A nucleotide in their promoter sequence.…”
mentioning
confidence: 99%